Revisiting History: Sorayya Khan’s Amorphous Noor and Memory - Katariya, Archana; Chaudhary, Priyanka (International Journal of Psychosocial Rehabilitation, 2020)
The one duty we owe to history is to rewrite it." – Oscar Wilde ‘The political is personal’; polity shapes all individuals for Sorayya Khan. History and politics are the superstructures that determine our affiliation and resistance among characters. The essay deciphers how the individual and collective decisions are shaped and affected by larger structures of polity and history. The novel opens with ‘words from Kashmiri poet Agha Shahid Ali: Your history gets in the way of my memory’. .Khan’s effort, in this novel, to shatter the implicit silence amid Pakistan nation-state and explore the gloomy legacy of Pakistanis through the uncanny and unerring art of eponymous Noor, not only implies to Ali and Sajida but also unlocks the ideology, hierarchy and politics within the boundaries of nationalism. The ‘memory is the means by which we draw on our past experiences in order to use this information in the present’ (Sternberg, 1999), which assists to resolve the unspoken stagnancy in the familial relations. This essay explores how individual memory grows into collective memory by leading the path of episodic memory, post-traumatic stress disorder and dreams to answer the marginal sufferers and the deeds carried out in nation-states as an exponential hierarchy. Concluding an in-depth study of the novel in light of the Bangladesh 1971 Liberation War and the theme of memory, this essay examines the textual and historical relationship, tracing the shift from the official national narrative to the psychological and directing the path from personal memory of community actions is logged into the larger collective memory of the country. In this analysis, how the trauma and its memory of 1971 inhabits, retrieved, both within and outside the individual to reconcile to familial relations and identity of a nation-state. Individual preferences are overshadowed by political existences.